Annual Report 2020 on EIB Activity in Africa, the Caribbean, the Pacific, and the Overseas Countries and Territories - European Investment Bank (European Investment Bank, 2021)
The European Investment Bank is helping African, Caribbean and Pacific countries in parts of society that are sometimes forgotten - young people, women and girls, small companies, rural villages. We are creating opportunities for everyone. In this report, you can meet the people who are making a difference for themselves and for others. There are stories on the COVID-19 pandemic as well as a wider range of healthcare challenges. We speak to the head of the United Nations Development Programme about the Sustainable Development Goals. There are stories about female entrepreneurs in the Dominican Republic and the financing of farmers in Malawi. What all the people and places have in common is the need for good advice and investment. Please read this annual report in conjunction with the financial statements.